Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s13063-019-3591-1
|View full text |Cite
|
Sign up to set email alerts
|

Virtual training leads to real acute physical, cognitive, and neural benefits on healthy adults: study protocol for a randomized controlled trial

Abstract: Background Keeping a certain level of physical activity has beneficial effects on the body itself but also, surprisingly, on cognition: specifically, physical high-intensity intermittent aerobic exercise (HIE) can show improvement on cognitive executive functions. Although, in some cases performing strength or aerobic training is problematic or not feasible. Immersive virtual reality (IVR) can induce the illusory feeling of ownership and agency over a moving virtual body, therefore showing comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Recent studies have shown that the illusory feeling of ownership and agency over the virtual body creates the necessary conditions to induce effects on the physiological (Martini et al, 2013;Kokkinara et al, 2016;Fossataro et al, 2020) or even components higher than the mere perceptual level, such as social (Peck et al, 2013;Banakou et al, 2018), neural (Seinfeld et al, 2021), or cognitive functions: concerning the latter, in our previous study, we demonstrated on young healthy participants acute improvement of cognitive (executive) functions after a high-intensity intermittent exercise performed exclusively by the considered-as-own virtual body (Burin et al, 2019c(Burin et al, , 2020. We argued that, despite the participants being completely still, the feeling of ownership and agency over the virtual body (only if displayed in a first-person perspective) (Kokkinara et al, 2016) induced a cascade of events (from the physiological activation of the heart rate to the increased neural activity over task-related areas), culminating in the improved cognitive performance immediately after the virtual exercise, comparable to what happens after a similar training performed by one's own physical body (Hyodo et al, 2016;Kujach et al, 2017).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recent studies have shown that the illusory feeling of ownership and agency over the virtual body creates the necessary conditions to induce effects on the physiological (Martini et al, 2013;Kokkinara et al, 2016;Fossataro et al, 2020) or even components higher than the mere perceptual level, such as social (Peck et al, 2013;Banakou et al, 2018), neural (Seinfeld et al, 2021), or cognitive functions: concerning the latter, in our previous study, we demonstrated on young healthy participants acute improvement of cognitive (executive) functions after a high-intensity intermittent exercise performed exclusively by the considered-as-own virtual body (Burin et al, 2019c(Burin et al, , 2020. We argued that, despite the participants being completely still, the feeling of ownership and agency over the virtual body (only if displayed in a first-person perspective) (Kokkinara et al, 2016) induced a cascade of events (from the physiological activation of the heart rate to the increased neural activity over task-related areas), culminating in the improved cognitive performance immediately after the virtual exercise, comparable to what happens after a similar training performed by one's own physical body (Hyodo et al, 2016;Kujach et al, 2017).…”
Section: Introductionmentioning
confidence: 76%
“…In the present study, in order to answer these questions, we adapted the same virtual training (Burin et al, 2019c(Burin et al, , 2020 to test its efficacy on a sample of 42 physically and neurologically healthy elderly (over 60 years old) and to compare the acute and long-term impacts on cognitive, physiological, and neural functions. We conducted a parallel-group randomized controlled trial (RCT) composed of a 6-week (twice a week) IVR intervention, each session including 20 min of virtual highintensity intermittent exercise (vHIE), alternating the avatar between fast walking and slowly walking every 2 min: while the participants were sitting still, they observed the virtual body, either in a first-person perspective (1PP, the experimental group) or a third-person perspective (3PP, the control group), performing the virtual exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining a certain level of physical activity has beneficial effects on the body itself but also, surprisingly, on cognition [65]. Despite new developments, a large portion of VR s potential is still unexplored; therefore, real experiences in a flexible context that combine relevant cultural, physical, and cognitive aspects are necessary [66].…”
Section: Discussionmentioning
confidence: 99%
“…VR has found multiple effective therapeutic uses in recent years, to increase exercise motivation [31], and to stimulate HR in stationary users [24,25]. Its use to encourage patients to complete therapeutic recovery regimens, sometimes called exergaming, is particularly welldeveloped [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The findings in Drosophila, coupled with the fact that epinephrine and norepinephrine increase during exercise in humans, and the fact that VR has been shown to be capable of increasing HR in stationary users [24,25], led us to propose that intermittent stimulation of adrenergic signaling might have therapeutic benefit in humans with a sedentary lifestyle [26].…”
Section: Introductionmentioning
confidence: 99%